First autochthone case of sporotrichosis by Sporothrix globosa in Portugal - Oliveira, Manoel Marques Evangelista de (2014)
In this study, we characterize the first autochthone case of human sporotrichosis reported in Lisbon, Portugal. Phenotypic and genotypic characterization revealed that the infection was caused by Sporothrbc globosa. We conclude that sporotrichosis may be underdiagnosed particularly in Southern Europe and suggest Portugal as an emerging area for this fungal infection.